Determinação voltamétrica de tiofenos e sulfetos em matrizes asfálticas empregando eletrodo de ouro em meio não aquoso - Goularte, Rayane Bueno (2016)
The sulfur compounds have been studied for many years due to their importance in chemical, biological and industrial areas. These compounds can also be found in matrices of oil and its derivatives, and among the groups, the most important are the sulfides, thiophenes and benzothiophenes. The determination of these compounds in asphalt has great importance since they are considered precursors of oxidation reactions and are directly related to its aging, which reflects the durability of pavements. Therefore, various methods for determining these compounds have been described, although there is a lack of information in the literature about studies of sulfur compounds employing voltammetry and gold electrode. Thus, the aim of this study was to develop an electrochemical method for determining organo-sulfur compounds in asphalt oil cement samples (CAP) using differential pulse voltammetry in non-aqueous medium, a gold electrode as working electrode, an Ag/AgCl reference electrode modified with LiCl saturated in ethanol and 0.1M NaClO4 in DMSO and a platinum wire as counter electrode, as a supporting electrolyte was used a 0.1M NaCl4 solution in DMSO.